New Ir Bis-Carbonyl Precursor for Water Oxidation Catalysis - Huang, DL (2016)
This research was supported by the Center for Catalytic Hydrocarbon Functionalization, Number DE-SC0001298 (D.L.H. and R.H.C.), and Argonne-Northwestern Solar Energy Research (ANSER), Number DE-SC0001059 (J.M.T., R.-B.S., K.L.M. and G.W.B.); both agencies are Energy Frontier Research Centers funded by the U.S. Department of Energy. D.L.H acknowledges support by the National Science Foundation Graduate Research Fellowship Program under Grant No. DGE-1122492 and the Yale Dox Summer Research Fellowship. R.-B.S. R. B.-S. acknowledges support from the Consejo Nacional de Ciencia, Tecnologia e Innovacio ́ ́n Tecnologica (CONCYTEC), and the Ponti ́ ficia Universidad Catolica del Peru ́ ́(PUCP). DLS measurements were conducted in the Yale Facility for Light Scattering. We thank Liam Sharninghausen for assistance with crystallography and Dr. Eric Paulson for assistance with DOSY NMR spectroscopy.